Effectiveness of EVA: a comparative study on industrial product companies in Malaysia / Ahmad Zoolhelmi Alias - Alias, Ahmad Zoolhelmi (2001)
Economic Value Added (EVA) was advocated by Stern Stewart and Co. in 1982. This study intended to identify any added value or added advantage in EVA compare to conventional methods such as percentage increase in net tangible assets, profit margin, return on assets (ROA) and return on equity (ROE) as a performance measurement. This study is conducted in Malaysian business environment, as results of the previous researches are mixed regarding the efficacy of EVA. A sample size of 78 companies from Industrial Product sector of KLSE main board had been selected. In analysis of performance ranking and correlation between stock return and financial parameters, the outcomes have proved that there is no added value or added advantage in EVA compared to conventional methods as a performance measurement. It is hoped that this study will give at least a basic idea of Economic Value Added and also explain correlation between financial parameters and stock return under Malaysian business environment.